The Transformational Leadership Model of Aesthetic Education Administrators in Colleges and Universities in Shenyang Under Liaoning Province - Hu Jiaxin,; Chanphong , Somsak; Howattanakul, Sutida (Journal of Roi Kaensarn Academi, 2024)
The objectives of this research were:(1)To examine the components and indicators of transformational leadership of aesthetic education administrators in colleges and universities in Shenyang under Liaoning Province .(2) To propose the transformational leadership model of aesthetic education administrators in colleges and universities in Shenyang under Liaoning Province .(3) To put forward the guidelines for improving the transformational leadership of aesthetic education administrators in colleges and universities in Shenyang under Liaoning Province . The research was a mixed methodology research. The population incluede 92 aesthetic education administrators and 920 aesthetic education teachers from 45 colleges and universities, totalling 1012. The sample size was determined by Krejcie and Morgan's Table (1970), obtained by multi-stage sampling method, totalling 285. The 9 key informants were the president in charge of aesthetic education in colleges and universities, the dean of Liberal education college, the administrator of the aesthetic education department, the subject leader of the aesthetic education department, obtained by purposive sampling method. The instruments used for data collection were semi structured interview form, a five-level rating scale questionnaire. The statistics used for data analysis were frequency, percentage, mean, Standard Deviation, Confirmatory Factor Analysis as well as content analysis was employed. The research findings revealed that: (1) In the transformational leadership of the aesthetic educational administrators in colleges and universities in Shenyang under Liaoning Province is divided into five components, namely, Inspirational Motivation, Individualized Care, Intellectual Foresight, Integration of cooperation between internal and external partners and Innovation Intelligence. (2) Model of the transformational leadership of aesthetic education administrators in colleges and universities in Shenyang under Liaoning Province fit with empirical data for all indicators. and (3) There were total 15 guidelines for improve the transformational leadership of the aesthetic educational administrators in colleges and universities in Shenyang under Liaoning Province.